HUBUNGAN JUMLAH LEUKOSIT DENGAN KEJADIAN PREEKLAMSIA DI RSUD DR. M. HAULUSSY AMBON TAHUN 2018 - Ali Akbar R Kibas; Vina Z Latuconsina; Merlin M Maelissa (Fakultas Kedokteran Universitas Pattimura, 2021)
Preeclampsia is a toxemia in old pregnancy marked by hypertension, edema, and proteinuria. The etiology of disease is unknown, but there are several theories that have been forward, one of which is the theory of inflammation associated with leukocytes. The main of this study is to figure out the relations of leukocytes count in patients with preeclampsia in RSUD dr. M. Haulussy Ambon in 2018. This research is an analytic study with a cross-sectional research design. Sampling of the study used total sampling with a number of samples that met the inclusion and exclusion criteria of 62 patients consisting of 26 pregnant women with preeclampsia and 36 pregnant women without preeclampsia. The result using Chi-Square test showed that there was no significant relation of leukocyte count in preeclampsia (p=0,063).